Saint Lucia. Significant Achievements 2023 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2024)
In 2023, Saint Lucia achieved significant milestones with the support of the Inter-American Institute for Cooperation on Agriculture (IICA). IICA played a pivotal role in advancing the small-scale commercial mushroom industry by providing capacity building resources and conducting a consumer survey on mushrooms. Collaborating with local partners, including The Mushroom Collective and The Embassy of the Republic of China, Taiwan, IICA facilitated the development of methodologies for farmer organizations and family farming characterization. Moreover, IICA enhanced the export capacities of micro, small, and medium enterprises (MSMEs) through resources like export-readiness checklists and engagement in the Caribbean Virtual Agri-Food Trade Mission. In pursuit of sustainable agriculture, IICA, in collaboration with Beausoleil Sustainable Agribusiness Group and with funding from GEF SGP-UNDP, designed and tested cocoa regenerative models. This initiative aimed to promote sustainable cocoa production methods replicable in other communities. Additionally, IICA supported the local and regional apiculture industry by participating in the Annual Hewannora Honey Show, alongside partners like the OECS Commission and Iyanola Apiculture Collective. These achievements signify a concerted effort towards agricultural development, sustainability, and economic empowerment in Saint Lucia.